Pengaruh Germinasi Kedelai terhadap Komposisi Proksimat dan Komponen Bioaktif IsoflavonTempe Segar dan Semangit - Made Astawan (Perum BULOG, 2020)
Tempe is a traditional food from Indonesian made from soybeans fermented with Rhizopus spp. Based on the fermentation time, tempeh is divided into fresh tempeh and semangit tempe. Purpose of this study to determine the difference in chemical composition between fresh tempe flour from germination soybean (SG) and non-germination (SNG) and semangit tempe flour made from germination soybean (TG) and non-germination (TNG). Stage of the research include soybean germination process for 24 hours, making fresh tempe (48 hours fermentation), making semangit tempeh (120 hours fermentation), the process of making fresh tempe flour and semangit tempe flour. Analysis carried out on all tempeh flour includes yield, proximate, crude fiber, antioxidants and isoflavones. The process of germination of soybean as a raw material and the addition of fermentation time had no significant effect (p> 0,05) on the nutritional component, but had a significant effect (p <0,05) on the isoflavone levels and antioxidant activity of fresh tempe flour and semangit tempe flour produced. TNG has the highest levels of isidlavone daidzein and genistein, which are 432,8 and 707,8 μg / g, respectively. TNG has the highest antioxidant capacity (IC50 value of 2109 ppm) which is significantly better than SG and SNG, but not significantly different from TG.